Sequenciamento direto de blocos: impactos, limitações e benefícios para aderência ao planejamento de lavra - Felipe Ribeiro Souza (2016)
Mining scheduling is an important mining planning procedure, which determines which material will be mined, in what quantity, and during which period. These variables are highly influenced by cash flow and can therefore lead to the success or failure of the undertaken. A classical methodology, initially proposed by Lerchs-Grossmann, definesthe total amount of material mined without considering the correct discount factor and the operational restrictions of this process. To suppress the inconsistencies of this methodology, Direct Block Sequencing (SDB) proposes to execute the planning in a moreefficient and precise manner, considering the main problems of the classical methodology: the discount rate and operational aspects are not present in the classical methodology. The SDB methodology is able to analyze each block individually and apply discount factor and operational constraints more assertively. This methodology is able, in a single step, to determine the sequencing since there is no need to determine final pit and pushbacks before the mining sequencing is established. The correct application of the discount rate is responsible for reducing the mineral reserves. The blocks mined in future times are settled to a correct discount factor that reduces their individual benefit function. In this way, the search for a better financial result promotes the choice of the richestblocks in order to contribute to the increase of the Net Present Value. The economic value grow is followed by operational constraints in order to determine a more assertive longterm scenario with direct block sequencing. The present dissertation proposes to elaborate a methodology of work in order to execute a more assertive mining plan considering the operational restrictions and the correct discount rate.